Drug treatment for obesity (2012)
Obesity is one of the most critical diseases of the 21st century, which is associated with other health problems such as type 2 diabetes, cardiovascular disease and reduced life expectancy, and a strong effect on the economy. Over time, have developed anti-obesity drugs which work in different ways: by suppressing appetite, altering metabolism or inhibiting absorption heat. However, these drugs have had serious concerns about the safety of commonly prescribed use derivative side effects, leading the recent withdrawal of sibutramine and rimonabant. As a result of these setbacks, there are few anti-obesity drugs accepted. Knowledge about the gut-brain axis help you understand how the gastro-entero pancreatic, related to a series of peptides and hormones involved in food regulation and the brain, specifically the hypothalamus as a central regulator of the states of hunger and anorexia or appetite and body weight thereby. These lead us to study those drugs that are under research and development as monotherapies and combinations to conclude that there are three drugs already approved by the Food and Drug Administration or by its acronym U.S. FDA (two of them recently approved in 2012) and others which will become accepted for therapeutic use.